Thiazole, triazole, thio- and semicarbazone derivatives - Promising moieties for drug development for the treatment of tuberculosis - Cauê Benito Scarim; Fernando Rogério Pavan (Elsevier, 2021)
Thiazole, triazole, thio and semicarbazones are privileged motifs that act as pharmacophores in bioactive compounds for various diseases, such as Tuberculosis (TB). Tuberculosis (TB) is an infectious disease caused mainly by Mycobacterium tuberculosis and was responsible for 4,000 deaths a day in 2019 worldwide. The resistance and the gap of new drugs is the main cause of the slow drop in TB infections. In this review article, we analyse recent contributions of thiazole, triazole, thio and semicarbazone scaffolds to anti-TB drugs. Beyond these recent trends, we demonstrate the potential of the thiazole, triazole, thio and semicarbazone approach in the medicinal chemistry field of anti-M. tuberculosis drug discovery.